Effect of Zinc Supplementation on Insulin Resistance, Lipid Profile, BMI in Type II Diabetic Patients - Ghusoon T. Witwit; Besmah M. Ali; Yasameen Alsaffar; Anmar D. Ghazala (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Zinc is one of the most important essential trace metals in human nutrition and lifestyle withspecial role in diabetic patients mainly due to its involvement in insulin production, storage and secretion.-Objectives: to assess the effect of zinc supplementation on changing insulin resistance ,modifying lipidprofile and body mass index(BMI) in type II diabetics.-Design and Setting: A randomized controlled clinicaltrial.-Study participants: the study was carried on 50 type II diabetic patients, both gender and followed for6 weeks. the participants were randomly divided into intervention group who receives 50 mg/d elementalzinc and control group without zinc supplement.-Materials: S. zinc, fasting plasma glucose(FPG), fastingS. insulin, HbA1c, lipid profile, BMI were measured at the beginning(before supplementation and at the endof the 6 weeks duration.Results: After 6 weeks of zinc supplementation, serum zinc levels improved significantly (P=0.0001). Therewas no significant difference in BMI (P=0.092). Insulin resistance (IR), HbA1c were significantly decreased(change mean -0.75 P=0.004 and -0.72, P=0.001) respectively. HDL-C was significantly increased (changemean 3.56 mg/dl P=0.022). TG and TC were significantly decreased (change mean-10.92mg/dl P=0.001 and– 3.52mg/dl P=0.009) respectively. There was significant positive correlation between zinc intake and serumzinc level (R2=0.432).-Conclusion: Our study results revealed that supplementation of 50 mg zinc sulphateimproves insulin resistance and induces more healthy lipid profile, while it has no significant effect on BMIof type II diabetic patients after 6 weeks of supplementation.